Rapunzel's revenge - Hale, Shannon. (Bloomsbury, 2008)
Rapunzel is raised in a grand villa surrounded by towering walls. Rapunzel dreams of a different mother than Gothel, the woman she calls Mother. She climbs over the wall and finds out the truth. Her real mother, Kate, is a slave in Gothel's gold mine. In this Old West retelling, Rapunzel uses her hair as a lasso and to take on outlaws--including Gothel.